Study of NOx Emissions of S.I. Engine Fueled with Different Kinds of Hydrocarbon Fuels and Hydrogen - Chaichan, Miqdam T.; Abass, Qahtan A. (Al-Khwarizmi Engineering Journal, 2010)
Liquefied petroleum gas (LPG), Natural gas (NG) and hydrogen were used to operate spark ignition internal combustion engine Ricardo E6, to compare NOx emissions emitted from the engine, with that emitted from engine fueled with gasoline as a fuel. The study was done when engine operated at HUCR for gasoline, compared with its operation at HUCR for each fuel. Compression ratio, equivalence ratio and spark timing were studied at constant speed 25rps. The results appeared that NOx concentrations will be at maximum value in the lean side near the stoichiometric ratio, and reduced with moving away from this ratio for mixture at both sides, these concentrations were at its highest value when hydrogen used at CR=8:1, and got near to each other for the three hydrocarbon fuels used in the study, when the engine operated at HUCR for each fuel, but still hydrogen had maximum value, the main variable affect these concentrations was spark timing.